Portuguese vs International Millennials: How do Their Conflict Management Styles Differ? - Falcão, P. F.; Lopes da Costa, R. (ICABM2020 - International Conference of Applied Business and Management, 2020)
The purpose of this paper is to analyze how conflict management styles are valued and used differently by Portuguese and International Millennials. A sample of 158 Portuguese people aged between 21 and 35 years old answered an online questionnaire comprehending demographic variables and validated questions using the DUTCH Test for Conflict Handling answered in a 5-point Likert scale. The proposed model is original in the sense that it assesses the preference of conflict management styles of Portuguese millennials, using the DUTCH Test for Conflict Handling and complemented by Hofstede's Theory of Cultural Dimensions. The results show that the Portuguese Millennials prefer conflict styles that show concern both for themselves and for other individuals. The order in which styles are preferred by the Portuguese Millennials is the following: Problem-Solving, Compromising, Yielding, Avoiding, and Forcing. These results were compared with the results of India and the U.S.A. If, on the one hand, the Styles of Conflict Management preferred by the Portuguese are like those of the Indians, on the other we cannot say that they have similar cultures. An Individualistic culture tends to use conflict management styles as Forcing or Yielding and in the case of a Collectivistic the preferred styles are Problem-Solving or Avoiding. This information is in accordance with the results presented for Portugal – a Collectivistic society in which the style that appears as the most scored is Problem-Solving – and for the U.S.A. – an Individualistic culture where Forcing comes first. However, in the case of India, no conclusions were derived as it is a society with both sides (Individualist and Collectivist).